Time to Recruitment for a Two Grade Manpower System by Max Policy of Recruitment - Parameswari, K.; Rajadurai, P.; Venkatesh, S. (International Journal of Engineering and Technology, 2018)
In this paper an organization with two different grades, the grade wise depletion of manpower occurs due to its policy decisions is considered. Using max policy of recruitment the system characteristics namely mean and variance of time to recruitment are obtained by considering two different forms of wastages. The influence of the nodal parameters on the system characteristics is studied.Â